Structure Functions and Activities - Planning Commission (Planning Commission, 1981)
Evaluation has been envisaged as an essential aspect of the formulation and execution of the development plans and programmes by the Planning Commission since the formulation of the First Five Year Plan. A reference to this need was made by the Planning Commission in its report on the First Five Year Plan, wherein it was stated that, “With every important programme provision should always be made for assessment of results. Systematic evaluation should become a normal administrative practice in all branches of public activity.” The Grow More Food Enquiry Committee which made a comprehensive review of agricultural development efforts in the post-independence years had also recommended that a permanent organisation should be set up to review the results of extension efforts. During the First Five Year Plan, the evaluation work was mainly concerned with the regular assessment of results through periodical reporting on Community Development Programme and arrangements for analysis and follow-up of the reports.
Programme Evaluation Organisation Planning Commission Government of India November, 1981